2006
DOI: 10.1142/s0217979206034406
|View full text |Cite
|
Sign up to set email alerts
|

Local Invariants and Pairwise Entanglement in Symmetric Multiqubit System

Abstract: Pairwise entanglement properties of a symmetric multi-qubit system are analyzed through a complete set of two-qubit local invariants. Collective features of entanglement, such as spin squeezing, are expressed in terms of invariants and a classification scheme for pairwise entanglement is proposed. The invariant criteria given here are shown to be related to the recently proposed (Phys. Rev. Lett. 95, 120502 (2005)) generalized spin squeezing inequalities for pairwise entanglement in symmetric multi-qubit state… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Spin squeezing has been an intense area of study due to its theoretical importance as well as the applicability of spin squeezed states in the fields of low noise, high precision spectroscopy [27][28][29] and quantum information science. [10,11,[13][14][15][16] The relative ease with which spin squeezed states can be produced, [10,26] has made them more accessible and hence useful in the concerned fields.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spin squeezing has been an intense area of study due to its theoretical importance as well as the applicability of spin squeezed states in the fields of low noise, high precision spectroscopy [27][28][29] and quantum information science. [10,11,[13][14][15][16] The relative ease with which spin squeezed states can be produced, [10,26] has made them more accessible and hence useful in the concerned fields.…”
Section: Introductionmentioning
confidence: 99%
“…[31,32] Recently, permutation symmetric states have received a revived attention in diverse branches of physics due to their geometrical intuition and experimental importance. [13,14,33,34] Dicke states |s, m , the common eigenstates of Ŝ2 , Ŝz belonging respectively to eigenvalues s(s + 1)h 2 , mh, m = −s, −s + 1, . .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] and [6], regarding the presence of quantum entanglement in a quantum system, forms an important step toward the understanding of quantum entanglement in the context of bipartite states. It has also been found that spin squeezing has a close relationship with quantum entanglement and a lot of work has been done in this direction [7][8][9][10][11][12][13]. A system that is in a spin squeezed state is also quantum mechanically entangled.…”
Section: Introductionmentioning
confidence: 99%